2023
DOI: 10.3390/jcm12031059
|View full text |Cite
|
Sign up to set email alerts
|

The sFlt-1/PlGF Ratio in Pregnant Patients Affected by COVID-19

Abstract: COVID-19 in pregnant women increases the risk of adverse pregnancy outcomes, including preeclampsia. This meta-analysis aimed to examine the effect of SARS-CoV-2 infection on sFlt-1/PIGF ratio during pregnancy. The study was designed as a systematic review and meta-analysis. PubMed, Web of Science, Embase and Cochrane Library were searched for relevant studies reporting the sFlt-1/PlGF ratio in pregnant women with COVID-19. Results were compared using meta-analysis by the Mantel–Haenszel method. A total of 7 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Meta-analysis conducted by Kosińska-Kaczyńska et al included of 7 studies, revealed that sFlt-1/PlGF ratios between COVID-19 positive vs. negative women were higher, 45.8 ± 50.3 vs. 37.4 ± 22.5, respectively (SMD = 1.76; 95% CI: 0.43 to 3.09; p = 0.01) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis conducted by Kosińska-Kaczyńska et al included of 7 studies, revealed that sFlt-1/PlGF ratios between COVID-19 positive vs. negative women were higher, 45.8 ± 50.3 vs. 37.4 ± 22.5, respectively (SMD = 1.76; 95% CI: 0.43 to 3.09; p = 0.01) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 affects the secretion of cytokines and growth factors [ 47 ]. The importance of biomarkers in diagnosing PE is becoming recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) 14 and nuclear erythroid-2 related factor 2 (Nrf2) 15 , which are responsible for maintaining the redox balance in cells and generating a response to an inflammation 16 . The SARS-CoV-2 virus enters host cells via the angiotensin-converting enzyme 2 (ACE2) receptor 17 , which decreases the expression of the angiotensin II type-2 receptor and the placental growth factor (PlGF), and increases the expression of the angiotensin II type-1 receptor and soluble fms-like tyrosine kinase-1 (sFlt-1) 18 , 19 . These processes can disrupt mitochondrial function and trigger the overproduction of ROS, including O 2 − , and RNS.…”
Section: Introductionmentioning
confidence: 99%